Rechargeable batteries : history, progress, and applications - Boddula, Rajender (Scrivener Publishing, Wiley, 2020)
"Battery technology is constantly changing, and the concepts and applications of these changes are rapidly becoming increasingly more important as more and more industries and individuals continue to make "greener" choices in their energy sources. As global dependence on fossil fuels slowly wanes, there is a heavier and heavier importance placed on cleaner power sources and methods for storing and transporting that power. Battery technology is a huge part of this global energy revolution. Rechargeable battery technologies have been a milestone for moving toward a fossil-fuel-free society. They include groundbreaking changes in energy storage, transportation, and electronics. Improvements in battery electrodes and electrolytes have been a remarkable development, and, in the last few years, rechargeable batteries have attracted significant interest from scientists as they are a boon for electric vehicles, laptops and computers, mobile phones, portable electronics, and grid-level electricity storage devices. Rechargeable Batteries: History, Progress, and Applicationsoutlines the history, development, future, and applications for rechargeable batteries for energy storage applications. It also provides an in-depth description of various energy storage materials and is an invaluable reference guide for electro-chemists, chemical engineers, students, faculty, and R & D professionals in energy storage science, material science, and renewable energy. This is a must-have for any engineer's library who works with batteries and energy storage"--